ANALISIS KEPADATAN ARUS LALU LINTAS DUA LAJUR SEARAH DENGAN MENGGUNAKAN MODEL KONTINUM SEDERHANA - Liza Alifiana (Jurnal Matematika, 2016)
ABSTRACT.Jalan Gombel Lama, Semarang is a two-lane road in the same direction. Theroadwas relatively dense even jammed at certain hours. In this thesis analyzed the value of density onthese roads by using a simple continuum model. Simple continuum model is one model of the flowof traffic lanes. This model explains the relationship speed, density, and traffic flow. This modelalso explains the interaction between the two lanes, where vehicles are driven on a lane can moveto the other lane that is more tenuous. Density values obtained by finding the numerical solution ofthe model using the finite difference method Lax Friedrichs. The solution is used to determine thevalue of the density on the road. From the data simulation density values obtained on both lanesalmost the same so that the value of the level of small displacement vehicles.Keywords:simple continuum model, Lax Friedrichs